Type-2 Fuzzy Logic in Control of Nonsmooth Systems Theoretical Concepts and Applications - Castillo, Oscar; Aguilar, Luis T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the synthesis and analysis of fuzzy controllers and its application to a class of mechanical systems. It mainly focuses on the use of type-2 fuzzy controllers to account for disturbances known as hard or nonsmooth nonlinearities. The book, which summarizes the authors' research on type-2 fuzzy logic and control of mechanical systems, presents models, simulation and experiments towards the control of servomotors with dead-zone and Coulomb friction, and the control of both wheeled mobile robots and a biped robot. Closed-loop systems are analyzed in the framework of smooth and nonsmooth Lyapunov functions.
Background on Type-1 and Type-2 Fuzzy Logic -- Genetic Algorithms -- Fuzzy Lyapunov Synthesis for Nonsmooth Mechanical Systems -- Fuzzy Control for Systems with Dead-Zone and Backlash -- Fuzzy Control Synthesis for Systems with Discontinuous Friction -- Fuzzy Control for Wheeled Mobile Robots -- Fuzzy Control for Biped Robots under Impacts.
Keywords: Computational intelligence; Control engineering; Multibody systems; Vibration; Mechanics, Applied; Robotics; Automation; Computational Intelligence; Control and Systems Theory; Multibody Systems and Mechanical Vibrations; Control, Robotics, Automation